2013
DOI: 10.4161/hv.22982
|View full text |Cite
|
Sign up to set email alerts
|

17DD yellow fever vaccine

Abstract: Objective: To verify if the Bio-Manguinhos 17DD yellow fever vaccine (17DD-YFV) used in lower doses is as immunogenic and safe as the current formulation.Results: Doses from 27,476 IU to 587 IU induced similar seroconversion rates and neutralizing antibodies geometric mean titers (GMTs). Immunity of those who seroconverted to YF was maintained for 10 mo. Reactogenicity was low for all groups.Methods: Young and healthy adult males (n = 900) were recruited and randomized into 6 groups, to receive de-escalating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 29 publications
6
56
0
2
Order By: Relevance
“…The fourth scenario is based on an experimental study [32] in which distinct doses of the YF vaccine were tested. Compared to the standard dose, the experimental study reported that, to some extent, the reduction did not significantly affect the percentage of sero-conversion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fourth scenario is based on an experimental study [32] in which distinct doses of the YF vaccine were tested. Compared to the standard dose, the experimental study reported that, to some extent, the reduction did not significantly affect the percentage of sero-conversion.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, computational experiments are executed several times, using distinct values for the vaccine doses. For comparison purposes, the computational experiments were carried out using the same values of the experimental study [32]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations